Dakwah Harmoni Komunitas: Studi Transformasi Identitas Kampung Muslim Dayak di Desa Semabi, Kecamatan Sekadau Hilir, Kabupaten Sekadau Kalimantan Barat - Abdul Halim; Baiti Rahmawati; Roisul Umam (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
This study reviews the Dayak ethnicity as an exotic ethnicity with a unique interior image. They are accustomed to 'hunting human heads for marriage plots'. Traditions like this are considered as an obligation to avoid danger and disaster, and become a symbol of power and manliness. However, the practice of 'head hunting' only applies when Islam has not touched the theology of the Dayak community with ancestral religion in the past. This study focuses on the struggle of the Dayak Senganan and Malays in the villages of Semabi, Sekadau Hilir, Sekadau, West Kalimantan, which relates to the stigma that, by embracing Islam it means revoking the 'worthiness' identity. To illustrate the transformation of Dayak Wealth identity The methodology used in this study is the ethnographic method. The term 'Wealth' is derived from the word 'right' which means the transition from left to right, namely by embracing Islam. Findings from this study indicate that the key to inter-citizen harmony is supported by the strength of harmony between religious elites and also local cultural elites, and the role of shared awareness to coexist becomes a benchmark of harmonization. The power of harmony built by these two elite figures has produced transformative propaganda based on tradition.